5. Complete the following. a) Simplify: i) \( \left(m+\frac{1}{m}\right)\left(m^{2}-1+\frac{1}{m^{2}}\right) \) ii) \( \left(m+\frac{1}{m}\right)^{2} \). b) If \( m+\frac{1}{m}=2 \), calculate the value of: i) \( m^{2}+\frac{1}{m^{2}} \) ii) \( m^{3}+\frac{1}{m^{3}} \)
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Bonus Knowledge
To tackle these problems, let's simplify and calculate step by step. a) i) First, simplify \( \left(m+\frac{1}{m}\right)\left(m^{2}-1+\frac{1}{m^{2}}\right) \). Starting with the first expression: \[ m^2 - 1 + \frac{1}{m^2} = (m^2 + \frac{1}{m^2}) - 1 \] Now, we recognize that \( m^2 + \frac{1}{m^2} \) can be derived from the identity \( (m + \frac{1}{m})^2 = m^2 + 2 + \frac{1}{m^2} \), so \( m^2 + \frac{1}{m^2} = (m+\frac{1}{m})^2 - 2 \). Then we substitute: \[ m^2 - 1 + \frac{1}{m^2} = (m+\frac{1}{m})^2 - 3 \] Substituting back, we get: \[ \left(m+\frac{1}{m}\right)\left((m+\frac{1}{m})^2 - 3\right) \] Let \( x = m+\frac{1}{m} \): \[ x (x^2 - 3) = x^3 - 3x \] ii) For \( \left(m+\frac{1}{m}\right)^{2} \): \[ \left(m+\frac{1}{m}\right)^{2} = m^2 + 2 + \frac{1}{m^2} \] So, it simplifies directly to: \[ m^2 + \frac{1}{m^2} + 2 \] b) i) If \( m+\frac{1}{m}=2 \), then substituting into the derived formula: \[ m^2 + \frac{1}{m^2} = (m+\frac{1}{m})^2 - 2 = 2^2 - 2 = 4 - 2 = 2 \] ii) To find \( m^{3}+\frac{1}{m^{3}} \), use the identity: \[ m^{3}+\frac{1}{m^{3}} = \left(m+\frac{1}{m}\right) \left(m^{2}+\frac{1}{m^{2}}\right) - (m+\frac{1}{m}) \] Substituting values: \[ m^{3}+\frac{1}{m^{3}} = 2 \cdot 2 - 2 = 4 - 2 = 2 \] Thus, summarizing the results: a) i) \( x^3 - 3x \) ii) \( m^2 + \frac{1}{m^2} + 2 \) b) i) 2 ii) 2